Parcerias pela sustentabilidade em contextos de complexidade. O caso do trabalho colaborativo no Programa Oeiras Solidária: https://doi.org/10.53809/TS_ISS_2023_n.4_158-173 ("Temas Sociais" Journal, 2023)
This article presents the main results of a case study of a social responsibility network in the Municipality of Oeiras and results from a dissertation in the Master of Social Policy. The research aimed to analyse how the companies participating in the network integrated collaborative work (within the scope of SDG 17) in their social responsibility activities.This article presents the main results of a case study of a social responsibility network in the Municipality of Oeiras and results from a Master of Social Policy. The research aimed to analyse how the companies participating in the network incorporated SDG 17 in their activities and its contribution to the well-being of the Oeiras community. The research was supported by a documental analysis of scientific and grey literature, as well as interviews with key actors of the network.The main results of the study allow us to point to the need to frame the actions of companies at the local level in the field of public policies, in particular Social Policy, through the collaborative work established with other social actors. It also highlighted the central role of local public administration entities in promoting relationships between actors and supporting the development of the companies' skills to act within the scope of the SDGs.